Chlorpromazine-Induced Severe Hyponatremia in 66 Years Old Patient - Sri Soenarti; Muchammad Kamal Hadi (Acta Medica Indonesiana, 2024)
Hyponatremia is a common clinical problem in older people. The aging process is usually accompanied by various maladaptations to stress in different organs and physiologic functions. Medications are often the cause of hyponatremia such as thiazide diuretics, antidepressants, antiepileptic and antipsychotics. Antipsychotics can lead to severe hyponatremia by the mechanism of the development of the syndrome of inappropriate antidiuretic hormone secretion (SIADH). We report a patient who presented with severe hyponatremia due to Chlorpromazine and improved after receiving corrective hyponatremia.